Realistic Galaxy Simulations: Feedback, Magnetic Fields and the ISM - Robinson, Hector (My University, 2021)
The evolution of galaxies rely on a wide variety of physics, and numerical simulations are one of the main tools used to study them. In this thesis we develop a framework for what models can be used to realistically simulate galaxies and study their evolution. We begin with setting specific requirements on the numerical resolution of galaxies, and then test the effects of different stellar feedback models on isolated disk galaxies. We then investigate the addition of magnetic fields into the simulations, and what role they play in determining the contents, behaviour, and star formation, within the interstellar medium of galaxies.
Keywords: galaxies; hydrodynamics; supernova; magnetic fields; magnetohydrodynamics; galaxy evolution; high performance computing